A DESCRIPTIVE STUDY ON THE STUDENTS' ABILITY IN WRITINGNARRATIVE TEXT AT THE SECOND YEAR OF SMA N 1 ANDONG, BOYOLALI - EKAWATI, MURNI (2011)
The research aims at describing the students' ability in writing narrative text at SMA N 1 Andong, describing the difficulties faced by the students, and describing the difficulties faced by the teacher. This study is descriptive qualitative. The object of the study is students' ability in writing narrative text at second year of senior high school (SMA) N 1 Andong. The data are taken from events, informant, and document. The data are collected by having observation, document and interview. The data are analyzed by using descriptive qualitative approach. The results of the research show that: 1) the students' ability in writing narrative text at SMA N 1 Andong is good. The highest score is 95, the lowest score is 55 and the mean score is 74.2. 2) The problem faced by the students in teaching writing are that the students have difficulties in expressing their idea to perform the story, the students' difficulties to combine the word to be sentence and to use the correct grammar and vocabularies. 3) the problem faced by the teacher in teaching writing, namely class management, limited time, different capability of the students, and unstable motivation of the students.